EVALUASI PENERAPAN NILAI CINTA DALAM PROSES PEMBELAJARAN PENDIDIKAN AGAMA ISLAM: KONSTRUKSI INDIKATOR, VALIDASI PSIKOMOTORIK, DAN IMPLIKASINYA TERHADAP PERILAKU PROSOSIAL SISWA - M. Iwan Saputra; Lubna; Mukhlis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to evaluate the implementation of the value of love in the learning process of Islamic Religious Education (PAI) as part of efforts to foster students’ religious and social character. This study employs a qualitative approach using the library research method. Data were obtained through the review of books, journal articles, and previous studies relevant to the focus of the research. Data analysis was conducted using a descriptive-interpretative approach to examine the theoretical construction of love value indicators, the evaluation model in the psychomotor domain, and its implications for students’ prosocial behavior. The findings indicate that the value of love in PAI learning encompasses spiritual, social, and ecological dimensions that can be operationalized into evaluation indicators. The internalization of the value of love has been shown to have a close relationship with the improvement of students’ prosocial behavior, such as empathy, cooperation, and social concern. These findings emphasize the importance of authentic evaluation in PAI learning oriented toward the formation of noble character.